Reduced ferritin levels in individuals with non‐O blood group: results from the Danish Blood Donor Study. Issue 12 (8th October 2017) - Rigas, Andreas S.; Berkfors, Adam A.; Pedersen, Ole B.; Sørensen, Erik; Nielsen, Kaspar R.; Larsen, Margit H.; Paarup, Helene M.; Wandall, Hans H.; Erikstrup, Christian; Hjalgrim, Henrik; Ullum, Henrik
Abstract : BACKGROUND: Genomewide association studies have reported alleles in the ABO locus to be associated with ferritin levels. These studies warrant the investigation of a possible association between the ABO blood group and ferritin levels. We aimed to explore if ABO blood group is associated with iron stores expressed as ferritin levels. STUDY DESIGN AND METHODS: Ferritin levels were measured at least once for 30, 595 Danish Blood Donor Study participants. Linear regression analyses were performed with the ABO blood group as explanatory variable and adjusted for age, number of donations 3 years before the ferritin measurement, and time since latest donation. In addition, a subanalysis was performed on 15, 280 individuals in which further adjustments for body mass index, smoking status, and C‐reactive protein levels were possible. Furthermore, logistic regression analyses were performed to determine if ABO blood group was associated with a ferritin level of less than 15 ng/mL. RESULTS: Non‐O blood group donors had lower ferritin levels than blood group O donors, regardless of sex. Accordingly, risk of ferritin level of less than 15 ng/mL was increased for individuals with non‐O blood group compared with O blood group. In subanalyses similar associations were observed, albeit in women the association between blood group and risk of a ferritin level below 15 ng/mL was no longer significant. ABO blood group was not associated with red blood cell indices such as mean cell volume and mean cell hemoglobin content. CONCLUSION: Donors with non‐O blood group have lower ferritin levels than donors with other blood groups.